Pemecahan Masalah pada Siswa Tarbiyatus Shibyan dengan Pendekatan RME - Khoirotunnisa, Anis Umi; Himmah, Faiqotul; Irnawati, Lailatul (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
This research aims to describe the improvement in mathematical problem solving in fourth grade students at MI Tarbiyatus Shibyan through the use of the RME approach. This type of research is Classroom Action Research (PTK) which is implemented over two cycles where each cycle consists of three meetings. Each meeting consists of four stages, which include: 1. Planning; 2. Acting; 3. Observing; and 4. Reflecting. The subjects in this research were fourth grade students at MI Tarbiyatus Shibyan Baureno. The data collection techniques used were through interviews, tests and observations. In the pre-cycle, the average student problem solving was 35 with a completion percentage of 0%. Furthermore, in cycle 1 the average increased to 61 with a completion percentage of 40% and in cycle II it increased again to 84 with a completion percentage of 90%. Thus, it can be concluded that the RME Approach is able to optimize students' mathematical problem solving in mathematics learning